Options for Nitriles Removal from C–C Cuts: 1. Via Adsorption - Maria M. Ramírez-Corredores; Zaida Hernández; Julia Guerra; Jaqueline Medina; Rosa Alvarez (Adsorption Science & Technology)
Light cuts from fluid catalyst cracking (FCC) units are commonly used as feedstocks for etherification units in oil refineries. These feedstocks contain nitriles and diolefins that poison the etherification catalyst. PDVSA Intevep has developed several methods for removing these nitriles. An adsorption-based option is discussed in this paper; two other options reported recently were based on catalytic conversions (Ramírez-Corredores et al. 2002, 2003). The oligomerization tendencies of the diolefins dictated the use of a rather inert adsorbent. Some of the critical features of this adsorbent and the adsorption process are discussed. The adsorbent design was based on a geometrical premise and on active non-acid sites to achieve a highly selective adsorbent with a high adsorption capacity for nitriles. Chemical shift was selected for the desorption stage of the removal process to preserve the active lifetime of the adsorbent in the treatment of reactive feedstocks. This was demonstrated to be both effective and beneficial.